Ethics in Using Artificial Intelligence for Communication: Understanding the Risks and Benefits - La Jaali (PT. Anagata Sembagi Education, 2025)
Artificial intelligence (AI) has transformed the modern communication landscape by offering various conveniences and efficiencies. However, the use of this technology also raises complex ethical challenges. This study aims to analyze the ethical benefits and risks of using AI in communication and identify necessary mitigation strategies. The method used was a systematic literature review of 20 scientific publications from 2021-2025 that discuss the ethical aspects of AI in various communication contexts. The results show that AI provides significant benefits in personalizing services, increasing the efficiency of business communications, expanding access to education and mental health services, and optimizing the user experience. However, the implementation of AI also presents serious risks related to data privacy and security, algorithmic bias that can lead to discrimination, a lack of transparency in decision-making, and the potential for copyright infringement and the spread of misinformation. To minimize these risks, ethical practices are needed that include transparency and accountability in AI implementation, the development of comprehensive regulations and ethical standards, and increasing public digital literacy. This study concludes that the use of AI in communication must be based on a strong ethical framework involving collaboration between technology developers, policymakers, and the public to ensure this technology provides optimal benefits while protecting the fundamental rights of users.